Anti-Psoriasis Effect of Diclofenac and Celecoxib Using the Tail Model for Psoriasis - Diana Ana-Maria Nițescu; Horia Păunescu; Alina Elena Ștefan; Laurențiu Coman; Corneliu Cristian Georgescu; Andrei Constantin Stoian; Daniela Gologan; Ion Fulga; Oana Andreia Coman (MDPI AG, 2022)
Non-steroidal anti-inflammatory drugs (NSAIDs) showed effects in some hyperproliferative dermatologic pathologies. The aim of the study is the assessment of anti-psoriasis effect of diclofenac and celecoxib using a mice tail model. The topical application of substances on the proximal mice tails was performed for two weeks. The effects on the epidermal granular layer and mean epidermal thickness (excluding the stratum corneum) were evaluated using hematoxylin-eosin staining. Orthokeratosis degree and percentual drug activity were calculated. A positive control group treated with tretinoin and two negative controls (white soft paraffin and untreated mice) were used. Orthokeratosis degree significantly increased in all the NSAIDs groups (celecoxib 1%, 2% and diclofenac 1%, 2%) and in the tretinoin 0.05% group, versus negative controls. Celecoxib 1% and 2%, tretinoin 0.05% and white soft paraffin significantly increased mean epidermal thickness, versus untreated mice. The values obtained in the case of celecoxib 2% ointment regarding the orthokeratosis degree and percentual drug activity are providing premises for further investigations regarding this effect and the mechanisms of action involved. Celecoxib 2% had the greatest percentual drug activity and is a promising substance for the anti-psoriasis topical treatment. Along with the COX-2 inhibition, celecoxib might have an anti-psoriasis effect by other independent mechanisms.